2015
DOI: 10.1371/journal.pone.0139456
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-23 Facilitates Thyroid Cancer Cell Migration and Invasion by Inhibiting SOCS4 Expression via MicroRNA-25

Abstract: Interleukin–23 (IL–23) is a conventional proinflammatory cytokine that plays a role in tumor progression by inducing inflammation in the tumor microenvironment. However, the role of IL–23 in thyroid cancer migration and invasion remains unclear. In the present study, we observed that the treatment with IL–23, induced migration and invasion in human thyroid cancer cells. Additional data demonstrate that SOCS4 negatively regulates IL-23-mediated migration and invasion. On investigating the mechanisms involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
2
26
1
Order By: Relevance
“…These microRNAs induced ESCC cell migration and invasion through NRIP1. While a number of reports have identified miRNAs' role in tumor proliferation, apoptosis, differentiation, invasion and metastasis [24][25][26], there are few reports of the function of miR-548 and miR-576. To our knowledge, there are two applicable studies of miR-548 and two studies that report the function of miR-576.…”
Section: Discussionmentioning
confidence: 99%
“…These microRNAs induced ESCC cell migration and invasion through NRIP1. While a number of reports have identified miRNAs' role in tumor proliferation, apoptosis, differentiation, invasion and metastasis [24][25][26], there are few reports of the function of miR-548 and miR-576. To our knowledge, there are two applicable studies of miR-548 and two studies that report the function of miR-576.…”
Section: Discussionmentioning
confidence: 99%
“…The data does however provide novel evidence that SOCS-4 plays an active role in the regulation of migration in these two cell types. A study on a thyroid cancer cell line has suggested that SOCS-4 has an inhibitory effect on migration and that inhibition of SOCS-4 by miR-25 could promote thyroid cancer cell migration 30 . In the current study, particularly in terms of HaCaT keratinocytes, suppression of SOCS−4 inhibited migration, indicating a pro-migratory role for SOCS-4 in this cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Mature microRNAs (miRNAs) and mRNA levels was detected by using qRT-PCR assays as described 37 . For miRNAs, total RNA was isolated using a mirVana miRNA isolation kit (Ambion).…”
Section: Quantitative Real-time Rt-pcr (Qrt-pcr)mentioning
confidence: 99%